Open Space Experimental Work for L-Band Mobile Satellite (MS) using a Simple and Low Cost Data Acquisition System - Abba, I.; Abidin, W.A.W.Z; Bong, V.P.; Othman, A.K.; Hong Ping, Kismet (IEEE, 2010)
Mobile satellite (MS) signal performance is affected by many factors such as ionospheric effect, multipath fading and shadowing effect. Satellites transmit signals at the same strength, but things like trees and buildings can obscure a signal beyond recognition. Some experimental works have been done using the existing geo-satellite system or airborne platform in the developed countries which is quite expensive and complicated. Very little data is represents less developed countries such as Africa and Asia. Therefore, a simple and low cost data acquisition system that can be used to carry out measurement of the MS signal performance is proposed. The experiment is carried out in open area with no obstruction of the direct wave. In addition, NMEA sentences will be used to obtain the required signal propagation parameters. The measurement is then performed to determine the relationship between the signal performance with respect to the elevation and azimuth angles. Results obtained from analysis will be used to determine the characteristics of the open space environment. This method can be used to encourage more experimental works in the less develop countries. Propagation data for the open space environment can be used as a reference to determine the MS signal quality for shadowing environments.